Contribution of the arms in the sprint start and their influence on force and velocity characteristics - Graham-Smith, P.; Natera, A.; Saunders, S. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this case study was to quantify the contribution of the arms in the sprint start and compare the difference in force and velocity characteristics when arm forces are not accounted for. One elite student athlete performed 6 starts with the same block position whilst forces were measured independently for front and rear legs and left and right hands. The arms were found to apply force for 0.14s, initiated a peak force of 593N (0.83 BW) and accounted for 18% of the total vertical impulse generated. Inclusion of the arm forces increased the first vertical peak force by 118N, movement time by 0.03s, vertical toe-off velocity by 0.6m/s and projection angle by 10 degrees. Differences in vertical velocity and projection angle were halved by modifying the vertical system load to BW at the onset of movement. Peak horizontal forces and velocities were similar.